2013
DOI: 10.1002/prot.24288
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of Toxoplasma gondii nucleoside triphosphate diphosphohydrolase 1 represents a conformational intermediate in the reductive activation mechanism of the tetrameric enzyme

Abstract: Toxoplasma gondii nucleoside triphosphate diphosphohydrolase (NTPDase) 1 was crystallized in an intermediate tetrameric conformation. The crystal structure is similar to that of T. gondii NTPDase3 and represents an inactive conformation as the activating disulfide bridge is not reduced and the active site cleft between the two domains of each monomer is open. However, the arrangement of the monomers within the tetramer differs from that of the inactive form of NTPDase3 and may represent an intermediate conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…The analysis of the crystal structure of Toxoplasma gondii NTPDase revealed that this enzyme suffers a reductive activation, where disulfide bridge reduction causes a conformational change and active site loop closure followed by correct positioning of the active site residues and enzymatic activation (Krug et al, 2013). In order to investigate whether the T. evansi enzyme follows the same mode of action, we have tested NTPDase activity in the presence and absence of reduction agent dithioerytrol (DTT) and confirmed the same velocity rates for both measurements, indicating that unlike the enzyme from T. gondii, the T. evansi enzyme does not follow a reductive activation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the crystal structure of Toxoplasma gondii NTPDase revealed that this enzyme suffers a reductive activation, where disulfide bridge reduction causes a conformational change and active site loop closure followed by correct positioning of the active site residues and enzymatic activation (Krug et al, 2013). In order to investigate whether the T. evansi enzyme follows the same mode of action, we have tested NTPDase activity in the presence and absence of reduction agent dithioerytrol (DTT) and confirmed the same velocity rates for both measurements, indicating that unlike the enzyme from T. gondii, the T. evansi enzyme does not follow a reductive activation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this compound is able to activate the TgNTPase in vitro. Similarly, DTT has been also shown to activate the TgNTPase protein in vitro and to trigger egress of tachyzoites [ 57 , 58 ]. Although the processes governing egress are not fully understood, intracellular calcium levels appear to trigger the abrupt exit of parasites from the PV, which is accompanied by a rapid decrease in host cell ATP mediated by TgNTPase activation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes occur in several organisms, including Toxoplasma gondii [3], T. cruzi [4], T. evansi [5], Trichomonas vaginalis [6], and Leishmania infantum [7]. NTPDase from parasites can hydrolyze extracellular nucleoside tri- and diphosphate, thereby affecting the host's immune response [810].…”
Section: Introductionmentioning
confidence: 99%